2016
DOI: 10.3402/jev.v5.29975
|View full text |Cite
|
Sign up to set email alerts
|

A novel multiplex bead‐based platform highlights the diversity of extracellular vesicles

Abstract: The surface protein composition of extracellular vesicles (EVs) is related to the originating cell and may play a role in vesicle function. Knowledge of the protein content of individual EVs is still limited because of the technical challenges to analyse small vesicles. Here, we introduce a novel multiplex bead-based platform to investigate up to 39 different surface markers in one sample. The combination of capture antibody beads with fluorescently labelled detection antibodies allows the analysis of EVs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
258
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(268 citation statements)
references
References 70 publications
9
258
1
Order By: Relevance
“…Similar findings were recently presented in a publication by Stranska et al, which demonstrated the absence of CD81 and TSG101 in plasma EVs isolated by membrane affinity [69]. Additionally, recent advances in the field have demonstrated that so-called exosome markers can also be present on other classes of EVs and that EV isolates are a heterogeneous mixture of various subpopulations with specific protein profiles [81,82]. It is therefore conceivable that isolation methods are biased towards only partially overlapping EV populations, resulting in different protein profiles.…”
Section: Discussionsupporting
confidence: 83%
“…Similar findings were recently presented in a publication by Stranska et al, which demonstrated the absence of CD81 and TSG101 in plasma EVs isolated by membrane affinity [69]. Additionally, recent advances in the field have demonstrated that so-called exosome markers can also be present on other classes of EVs and that EV isolates are a heterogeneous mixture of various subpopulations with specific protein profiles [81,82]. It is therefore conceivable that isolation methods are biased towards only partially overlapping EV populations, resulting in different protein profiles.…”
Section: Discussionsupporting
confidence: 83%
“…In a similar vein, the 10 major device companies, skilled in flow technologies for cell analyses, have explored adaptations to EV studies towards “liquid biopsy” and longitudinal monitoring of personalized therapies. EVs are analysed using NTA, TRPS, SPR, atomic force microscopy, cryo-electron microscopy and others [26], and device manufacturers are providing flow cytometry approaches for quantitative particle-by-particle multiplex analyses of EVs [27]. Flow-cytometry resolution can approach 20 nm, and reagent EV and antibody standards are emerging to enable replication studies.…”
Section: Resultsmentioning
confidence: 99%
“…For example, MHC II is found on EVs secreted by antigen presenting cells (APC) [35,47]. As another example, CD2, CD8 and CD56 were found in EVs derived from natural killer (NK) cells and not in EVs derived from platelets where the opposite holds true for CD41b, CD42a and CD61 [48].…”
Section: Biogenesis Cargo Loading and Compositionmentioning
confidence: 99%